Modeling and Control of Dialysis Systems Volume 2: Biofeedback Systems and Soft Computing Techniques of Dialysis - Azar, Ahmad Taher. (Studies in Computational Intelligence, 2013)
This book is the first text of its kind that presents both the traditional and the modern aspects of dialysis modeling and control in a clear, insightful and highly comprehensive writing style. It provides an in-depth analysis of the mathematical models and algorithms, and demonstrates their applications in real world problems of significant complexity. It explains concepts in a clear, matter-of-fact style. The material of this book will be useful to advanced undergraduate and graduate biomedical engineering students. Also, researchers and practitioners in the field of dialysis, control systems, soft computing will benefit from it. In order to make the reader aware of the applied side of the subject, the book includes: Chapter openers with a chapter outline, chapter objectives, key terms list, and abstract. Solved numerical examples to illustrate the application of a particular concept, and also to encourage good problem-solving skills. More than 1000 questions to give the readers a better insight to the subject. Case studies to understand the significance of the joint usage of the dialysis modeling and control techniques in interesting problems of the real world. latest information, including latest research surveys and references related to the subjects